Correction: Toward realistic computer modeling of paraffin-based composite materials: critical assessment of atomic-scale models of paraffins. Issue 52 (24th August 2020) - Volgin, Igor V.; Glova, Artyom D.; Nazarychev, Victor M.; Larin, Sergey V.; Lyulin, Sergey V.; Gurtovenko, Andrey A.
Abstract : Correction for 'Toward realistic computer modeling of paraffin-based composite materials: critical assessment of atomic-scale models of paraffins' by Artyom D. Glova et al., RSC Adv., 2019, 9, 38834–38847, DOI: ; 10.1039/C9RA07325F .